Teaching Parallel and Distributed Computing Concepts in Simulation with WRENCH - Tanaka, Ryan; Ferreira da Silva, Rafael; Casanova, Henri (2019 IEEE/ACM Workshop on Education for High-Performance Computing (EduHPC), 2019)
Teaching topics related to high performance computing and parallel and distributed computing in a hands-on manner is challenging, especially at introductory, undergraduate levels. There is a participation challenge due to the need to secure access to a platform on which students can learn via hands-on activities, which is not always possible. There are also pedagogic challenges. For instance, any particular platform provided to students imposes constraints on which learning objectives can be achieved. These challenges become steeper as the topics being taught target more heterogeneous, more distributed, and/or larger platforms, as needed to prepare students for using and developing Cyberinfrastructure. To address the above challenges, we have developed a set of pedagogic activities that can be integrated piecemeal in university courses, starting at freshman levels. These activities use simulation so that students can experience hands-on any relevant application and platform scenarios. This is achieved by capitalizing on the capabilities of the WRENCH and SimGrid simulation frameworks. After describing our approach and the pedagogic activities currently available, we present results from an evaluation performed in an undergraduate university course.